New insecticide molecules and entomopathogens against Hadda beetle, Henosepilachna vigintioctopunctata infesting vegetable cowpea - Kodandaram, M H; Halder, Jaydeep; Rai, A B (Indian Journal of Plant Protection, 2020)
Laboratory and field experiments on the efficacy of novel insecticide molecules and entomopathogens to hadda beetle, Henosepilachna vigintioctopunctata were conducted at Indian Institute of Vegetable Research, Varanasi for two seasons during 2010-11. Chlorantraniliprole 18.5 SC @ 150 g a.i /ha and thiacloprid 21.7 SC @ 70 g a.i. /ha exhibited ovicidal action with lowest per cent egg hatching. Imidacloprid 17.8 SL @ 25 g a.i. /ha and thiacloprid 21.8 SC @ 70 a.i. /ha were found to be most effective against grub and adult stages of hadda beetle and recorded highest per cent mortality when tested by leaf residue method. Among the biopesticides viz., Metarhizium anisopliae (1x108 cfu/g) and neem oil provided highest protection over control and indicated compatibility and synergistic activity at 1:1 combination. Emamectin benzoate 5 SG @ 10 g a.i. /ha and thiodicarb 75 WP @70g a.i. /ha proved to be the most effective with highest reduction in pest population of 75.3 and 73.9%, respectively under field conditions.